Alternative nitrate reduction pathways in sandy sediments hosting Submarine Groundwater Discharge (SGD) - Severino Pino Ibánhez, Juan (Trinity College (Dublin, Ireland). Department of Geography, 2012)
Submarine Groundwater Discharge (SGD) is now recognized as an important transport vector of nutrients to the coastal ocean. The role of benthic sandy ecosystems in mitigating SGD NO3- loads to coastal marine ecosystems is uncertain. I used a combination of in-situ sampling, experiments under controlled conditions and detenninistic modeling techniques in order to identify, quantify and parameterize key biogeochemical processes of N in permeable sediments hosting SGD and thus elucidate the mediation role of SGD seepage faces over N fluxes to the coastal ocean.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin